2022
DOI: 10.3390/foods11233941
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Effects of Puerarin on Glucose and Lipid Metabolism in Metabolic Syndrome: Mechanisms and Opportunities

Abstract: Chronic diseases, including metabolic syndrome related to sugar and lipid metabolic disorders, are the leading causes of premature death around the world. Novel treatment strategies without undesirable effects are urgently needed. As a natural functional ingredient, puerarin is a promising alternative for the treatment of sugar and lipid metabolic disorders. However, the applications of puerarin are limited due to its poor solubility and short half-life. Various drug delivery systems have been investigated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…In recent years, numerous studies have demonstrated the beneficial effects of PUE on the regulation of glucose and lipid metabolism [12,13]. A review indicates that PUE is effective in mitigating the initiation and progression of various diseases, including obesity, diabetes, hypertension, atherosclerosis, cardiac ischemia, cardiac arrhythmia, cardiac hypertrophy, ischemic stroke, and cognition decline, by reducing oxidative stress and inflammation [12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In recent years, numerous studies have demonstrated the beneficial effects of PUE on the regulation of glucose and lipid metabolism [12,13]. A review indicates that PUE is effective in mitigating the initiation and progression of various diseases, including obesity, diabetes, hypertension, atherosclerosis, cardiac ischemia, cardiac arrhythmia, cardiac hypertrophy, ischemic stroke, and cognition decline, by reducing oxidative stress and inflammation [12].…”
Section: Discussionmentioning
confidence: 99%
“…However, dietary supplementation with PUE ameliorated these alterations induced by the HFHS diet. A review has summarized the mechanisms by which PUE regulates glucose and lipid metabolism both in vivo and vitro [13]. These…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations